Rizatriptan-Loaded Oral Fast Dissolving Films: Design and Characterizations - Shah, Kiramat Ali; Li, Guifeng; Song, Lina; Gao, Binbin; Huang, Linyu; Luan, Dazhi; Iqbal, Haroon; Cao, Qingri; Menaa, Farid; Lee, Beom Jin; Alnasser, Sulaiman M.; Alshahrani, Sultan M.; et al. (Pharmaceutics, 2022)
Rizatriptan (RZT) is an efficient anti-migraine drug which belongs to the class of selective 5 HT (1B/1D) serotonin receptor agonists. Nevertheless, RZT elicits several adverse effects and RZT nasal sprays have a limited half-life, requiring repeated doses that could cause patient noncompliance or harm to the nasopharynx and cilia. The current research aimed to develop orally disintegrating films (ODFs) of RZT employing maltodextrin (MTX) and pullulan (PUL) as film-forming polymers, as well as propylene glycol (PG) as a plasticizer. The ODFs were prepared by solvent casting method (SCM). The technique was optimized using Box–Behnken design (BBD), contemplating the ratios of PUL: MTX and different levels of PG (%) as factor variables. The influence of these factors was systematically analyzed on the selected dependent variables, including film thickness, disintegration time (D-time), folding endurance (FE), tensile strength (TS), percent elongation (%E), moisture content (%), and water uptake (%). In addition, the surface morphology, solid state analysis, drug content uniformity (%), drug release (%), and pH of the RZT-ODFs were also studied. The results demonstrated a satisfactory stable RZT-ODFs formulation that exhibited surface homogeneity and amorphous RZT in films with no discernible interactions between the model drug and polymeric materials. The optimized film showed a rapid D-time of 16 s and remarkable mechanical features. The in vitro dissolution kinetics showed that 100% RZT was released from optimized film compared to 61% RZT released from conventional RZT formulation in the initial 5 min. An animal pharmacokinetic (PK) investigation revealed that RZT-ODFs had a shorter time to achieve peak plasma concentration (Tmax), a higher maximum plasma concentration (Cmax), and area under the curve (AUC0−t) than traditional oral mini capsules. These findings proposed a progressive approach for developing anti-migraine drugs that could be useful in reducing the complications of dysphagia in geriatric and pediatric sufferers.
Keywords: maltodextrin; oral disintegrating films; propylene glycol; pullulan; rizatriptan; solvent casting method